Epidemiological study and genetic characterization of inherited muscle diseases in a northern Spanish region - Inmaculada Pagola-Lorz; Esther Vicente; Berta Ibáñez; Laura Torné; Itsaso Elizalde-Beiras; Virginia Garcia-Solaesa; Fermín García; Josu Delfrade; Ivonne Jericó (Orphanet Journal of Rare Diseases, 2019)
Abstract Background Inherited muscle diseases are a group of rare heterogeneous muscle conditions with great impact on quality of life, for which variable prevalence has previously been reported, probably due to case selection bias. The aim of this study is to estimate the overall and selective prevalence rates of inherited muscle diseases in a northern Spanish region and to describe their demographic and genetic features. Retrospective identification of patients with inherited muscle diseases between 2000 and 2015 from multiple data sources. Demographic and molecular data were registered. Results On January 1, 2016, the overall prevalence of inherited muscle diseases was 59.00/ 100,000 inhabitants (CI 95%; 53.35–65.26). Prevalence was significantly greater in men (67.33/100,000) in comparison to women (50.80/100,000) (p = 0.006). The highest value was seen in the age range between 45 and 54 (91.32/100,000) years. Myotonic dystrophy type 1 was the most common condition (35.90/100,000), followed by facioscapulohumeral muscular dystrophy (5.15/100,000) and limb-girdle muscular dystrophy type 2A (2.5/100,000). Conclusions Prevalence of inherited muscle diseases in Navarre is high in comparison with the data reported for other geographical regions. Standard procedures and analyses of multiple data sources are needed for epidemiological studies of this heterogeneous group of diseases.